Moniezia benedeni drives the SNAP-25 expression of the enteric nerves in sheep's small intestine - Zhen Huang; Wanling Yao; Wanhong He; Jing Pan; Wenzhu Chai; Baoshan Wang; Zhitao Jia; Xiping Fan; Wenhui Wang; Wangdong Zhang (BMC Veterinary Research, 2024)
Abstract Background The neuroimmune network plays a crucial role in regulating mucosal immune homeostasis within the digestive tract. Synaptosome-associated protein 25 (SNAP-25) is a presynaptic membrane-binding protein that activates ILC2s, initiating the host's anti-parasitic immune response. Methods To investigate the effect of Moniezia benedeni (M. benedeni) infection on the distribution of SNAP-25 in the sheep's small intestine, the recombinant plasmid pET-28a-SNAP-25 was constructed and expressed in BL21, yielding the recombinant protein. Then, the rabbit anti-sheep SNAP-25 polyclonal antibody was prepared and immunofluorescence staining was performed with it. The expression levels of SNAP-25 in the intestines of normal and M. benedeni-infected sheep were detected by ELISA. Results The results showed that the SNAP-25 recombinant protein was 29.3 KDa, the titer of the prepared immune serum reached 1:128,000. It was demonstrated that the rabbit anti-sheep SNAP-25 polyclonal antibody could bind to the natural protein of sheep SNAP-25 specifically. The expression levels of SNAP-25 in the sheep's small intestine revealed its primary presence in the muscular layer and lamina propria, particularly around nerve fibers surrounding the intestinal glands. Average expression levels in the duodenum, jejunum, and ileum were 130.32 pg/mg, 185.71 pg/mg, and 172.68 pg/mg, respectively. Under conditions of M. benedeni infection, the spatial distribution of SNAP-25-expressing nerve fibers remained consistent, but its expression level in each intestine segment was increased significantly (P < 0.05), up to 262.02 pg/mg, 276.84 pg/mg, and 326.65 pg/mg in the duodenum, jejunum, and ileum, and it was increased by 101.06%, 49.07%, and 89.16% respectively. Conclusions These findings suggest that M. benedeni could induce the SNAP-25 expression levels in sheep's intestinal nerves significantly. The results lay a foundation for further exploration of the molecular mechanism by which the gastrointestinal nerve-mucosal immune network perceives parasites in sheep.